KARAKTERISTIK ORGANOLEPTIK DAN FISIKO KIMIA ES KRIM RUMPUT LAUT DAN TEPUNG SAGU - Raja. B.D. Sormin; Maggie Christi Lakalay; Vonda M. N Lalopua (INASUA: Jurnal Teknologi Hasil Perikanan, 2026)
ABSTRACT The seaweed Eucheuma cottonii has been cultivated and developed as a source of carrageenan. One of its applications in the food industry is as a stabilizing agent. Common stabilizers used in ice cream production include CMC, guar gum, alginate, locust bean gum, and xanthan gum. However, these ingredients are expensive and difficult to obtain. The use of E. cottonii as a carrageenan source, combined with sago flour as a stabilizer in ice cream, is considered more economical due to its affordability and availability. This study was objected to determine the physicochemical and organoleptic characteristics of ice cream with the addition of E. cottonii puree and sago flour. The research method used is an experimental approach where consist of ice cream formulations: A0 used cornstarch; where A1, A2, A3: was the combinations of cornstarch, seaweed puree, and sago flour with ratio of (1:1:1), (3:1:2), and (3:2:1), respectively. A total of 50 grams of stabilizer was used in each formulation, along with additional ingredients such as skim milk, full cream milk, eggs, water, SP (emulsifier), and sugar. Observations included overrun testing, melting rate, and fat content. Organoleptic tests evaluated were color, aroma, taste, and texture. The results showed that the best physicochemical characteristics were found in formula A3 (cornstarch: seaweed puree: sago flour in a ratio 3:2:1), with an overrun value of 83.64%, a melting rate of 2.54 minutes per gram, and a fat content of 5.3%. Panelists preferred the color of formula A0, while for aroma, taste, and texture, they favored formula A2 (cornstarch: seaweed puree: sago flour with a ratio of 3:1:2).